THE INFLUENCE OF ASSET GROWTH, CAPITAL ADEQUACY RATIO (CAR) AND OPERATING COST OF OPERATING INCOME (BOPO) ON PERFORMANCE ISLAMIC FINANCE IN INDONESIA - Anjasmara, Dimas; Rokan, Mustafa Kamal; Hasibuan, Reni Ria Armayani (J-ISCAN: Journal of Islamic Accounting Research, 2024)
Financial institution produces financial statements that reflect its financial condition. Financialperformance is assessed through ratios within these statements, one of which is the profitabilityratio. The profitability ratio indicates the amount of profit earned by the company, evaluatinghow efficiently management can generate profit from each sale made. This study aims to examinethe effect of Asset Growth, CAR (Capital Adequacy Ratio), and BOPO (Operating Expenses toOperating Income) on ROA (Return on Assets). The population in this research consists of sevencompanies listed under Indonesian Islamic Commercial Banks. The data analysis methodsemployed include Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple LinearRegression Analysis, and Hypothesis Testing. Based on the T-test results, Asset Growth has avalue of 0.048 <0.05, indicating that Asset Growth significantly affects ROA. The CAR variablehas a significance value of 0.359>0.05, meaning that CAR does not have a significant effect onROA. BOPO significantly affects ROA with a significance value of 0.000<0.05. Furthermore, theSimultaneous Test (F) shows that Asset Growth, CAR, and BOPO collectively have a significanteffect on ROA, with a significance value of 0.000<0.05.